THE SINGLE MEDICAL SPACE IN THE PARADIGM OF ENSURING THE RIGHT TO PRACTICE IN TRADITIONAL AND ALTERNATIVE MEDICINE - Sopilko, Iryna; Yamnenko, Tetiana (Scientific works of Kyiv Aviation Institute. Series Law Journal "Air and Space Law", 2022)
Objective: to define the term «traditional and alternative medicine», to explore the mechanism of legal regulation of traditional and alternative medicine. Research methods: documentary analysis and synthesis, comparative analysis, objective truth, cognitive-analytical, etc. Results: the most effective mechanisms for solving problematic issues related to the exercise of the right to practice traditional and alternative medicine are described and revealed. Also, a way to solve problems related to the formation of a single medical space, which should be carried out within the paradigm of medical law of Ukraine. This is important for the single medical space, for the practice of traditional and alternative medicine and for the formation of medical law. Discussion: the possibility of applying different doctrinal approaches to the explanation of the concepts of traditional and alternative medicine and the application of the legal mechanism to these concepts.